Sildenafil drug as a safe anticorrosion for 6063 aluminum alloy in acidic and alkaline solutions: Theoretical and experimental studies - M. Abdallah; Mohamed I. Awad; H.M. Altass; Moataz Morad; Mona A. Eletre; Jabir H. Al-Fahemi; Wafa M. Sayed (Egyptian Journal of Petroleum)
The corrosion inhibition of aluminum alloy surface (6063AA) by Sildenafil (SIL) in 1 M for both HCl and NaOH solutions was investigated using weight loss, electrochemical techniques and quantum calculations. The inhibitory effect of SIL was explained by the formation of the complex adsorbed on the 6063AA surface. The adsorption obeyed Langmuir isotherm. The adsorption of the SIL is a mix of physical and chemical adsorption, where the free energy of adsorption was found to equal −39.12 and −34.6 KJ/mol, in HCl and NaOH, respectively. Experimental outcomes showed that SIL significantly inhibits the dissolution of 6063Al in both acidic and alkaline media. SIL drug acts as a mixed inhibitor in both two aggressive solutions. The correlation of the inhibition performance of SIL on 6063Al with the molecular structure was adopted using Dmol3 (Materials Studio v7. 0) based on some descriptors as EHOMO and ELUMO. Fukui indices were computed to determine the active sites of the inhibitor molecules. The equilibrium adsorption behavior of SIL on Al (111) surface was examined using molecular dynamics simulation. The quantum chemical descriptors were found suitable in explaining the inhibitive action of SIL.